Integrasi Teori Pembelajaran Dalam Pendidikan Agama Islam - Yahya Aminuddin; Wahyuni Iskandar; Syarif Syarif; Saprin Saprin (Universitas Islam Darud Da'wah Wal-Irsyad A.G.H. Abdurrahman Ambo Dalle, 2025)
This study aims to examine the form and meaning of the application of learning theories in the process of Islamic Religious Education (IRE), as well as how the implementation of these theories can improve learning efficiency and character building of students. This study focuses on the combination of various learning methods to achieve comprehensive Islamic education, covering cognitive, affective, and psychomotor dimensions. The approach used is qualitative research through literature study. Information is obtained by reviewing various scientific literature sources, such as books, journals, and articles related to learning theory and Islamic education. The data is then analyzed descriptively to find patterns of integration and their impact in the context of PAI (Islamic Religious Education) learning. The research findings reveal that combining behaviorism, cognitivism, constructivism, and humanism learning theories can improve the effectiveness of Islamic education. Behaviorist theory helps build learning habits and discipline; cognitive theory strengthens understanding and reasoning of Islamic teachings; constructivist theory encourages active student participation in building religious knowledge; while humanistic theory emphasizes the development of Islamic potential and personality as a whole.